1977
DOI: 10.2136/sssaj1977.03615995004100050011x
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Aluminosilicates, Aluminum Hydrous Oxides, and Aluminum Oxide with o‐Phosphate: The Formation of X‐ray Amorphous Analogs of Variscite and Montebrasite

Abstract: The formation of X‐ray amorphous analogs of variscite and Namontebrasite was demonstrated to occur when Al2O3 · nH2O, synthetic allophanes, and allophanic soils were reacted with sodium o‐phosphates, Na3‐AHAPO4, of varying acidity A. The formation of the two amorphous Al‐phosphates, Al(OH)2H2PO4 and AlOHNaPO4, respectively, was favored both by an increase in lability of Al (i.e., by large values of the hydration number n in Al2O3·nH2O or the presence of Si‐O‐Al bonds in the aluminosilicates) and by an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 0 publications
3
27
0
Order By: Relevance
“…Therefore, we could conclude that the Al(OH) 3 reacted with phosphate by the precipitation mechanism. The result was consistent with that from Veith and Sposito [42], who proposed that the precipitate formed during the phosphate adsorption onto Al(OH) 3 was an amorphous analog of variscite. Lookman et al [43] found the formation of an amorphous aluminum phosphate phase on the Al(OH) 3 surface through 27 Al and 31 P solid-state MAS NMR.…”
Section: Page 18 Of 44supporting
confidence: 91%
“…Therefore, we could conclude that the Al(OH) 3 reacted with phosphate by the precipitation mechanism. The result was consistent with that from Veith and Sposito [42], who proposed that the precipitate formed during the phosphate adsorption onto Al(OH) 3 was an amorphous analog of variscite. Lookman et al [43] found the formation of an amorphous aluminum phosphate phase on the Al(OH) 3 surface through 27 Al and 31 P solid-state MAS NMR.…”
Section: Page 18 Of 44supporting
confidence: 91%
“…This AI-P gel is also observed when P is applied to clay fractions of pumice (Nanzyo 1988) and allophanic Andisols (Nanzyo 1987). Veith and Sposito (1977b) suggested the formation of X-ray amorphous analogs of variscite (Al(OH)2H2P04) and montebrasite (AIOHNaP0 4 ) when AIP3·nHp, synthetic allophanes, and allophanic soils reacted with P. Although the formation of surface complexes (adsorption) and precipitates should be differentiated, both reactions (sorption) are likely to be based on the same kind of ligand exchange reaction of aquo or hydroxo ions on Al and / or Fe with P. These P sorption characteristics might be basically identical among all forms of Al and Fe in soils. However, co-existing SOM in soils may affect the P sorption characteristics, because SOM could be sorbed on metal (hydr)oxides by the same mechanism as P (Parfitt et al 1977;Stevenson 1994).…”
mentioning
confidence: 68%
“…Veith and Sposito [21] have also suggested a similar dissociation of adsorbed water (H 2 O) on AlPO 4 and FePO 4 .…”
Section: Characterization Of Crpomentioning
confidence: 82%